2009
DOI: 10.1177/00333549091240s206
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Surveillance for STDs, HIV, Hepatitis, and TB: A Survey of U.S. STD Control Programs

Abstract: Most STD control programs in the United States have some experience integrating surveillance data, but the degree of integration varies widely. Specific barriers to further integration were identified. The Centers for Disease Control and Prevention can help address these barriers by facilitating access to information and sharing technical solutions. Local and state programs can continue advancing surveillance integration by improving understanding of where integrated data are needed, increasing the use of avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…20 Another major challenge is the lack of integrated data management systems that span HIV surveillance and clinical care activities; integrating these would facilitate measurement of steps in the HIV care continuum. 58 Longitudinal studies could examine how women drug users move in and out of the HIV care continuum particularly since it may not be a linear process, especially for people living with multiple morbidities. In addition, since ART treatment thresholds vary across countries, it is important to ensure that pre-ART care is monitored and tracked over time.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another major challenge is the lack of integrated data management systems that span HIV surveillance and clinical care activities; integrating these would facilitate measurement of steps in the HIV care continuum. 58 Longitudinal studies could examine how women drug users move in and out of the HIV care continuum particularly since it may not be a linear process, especially for people living with multiple morbidities. In addition, since ART treatment thresholds vary across countries, it is important to ensure that pre-ART care is monitored and tracked over time.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunities around integrating surveillance data to help direct interventions and resources are highlighted in other publications, [12][13][14] as is the success of locally driven initiatives to integrate, match, and share data. 12,15,16 However, the findings in this study of APRs showed that only 20% (n512) of health departments shared data with another health department program. A 2009 survey of 47 federally funded STD programs found that 28% reported having "limited integration," defined as maintaining separate surveillance systems but comparing select data to guide interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of challenges to integrated surveillance. In a 2007 survey of CDC-funded STI programs that examined the extent of surveillance integration in these programs (18), barriers to increased integration were first identified and included the following: restrictive data policies, particularly for HIV data that are siloed from other systems; incompatible databases, which complicated the linking of data; lack of time and technical expertise in linking and managing data systems; and lack of financial resourcing. Subsequent to this survey, the CDC published guidelines for STBBI data security and confidentiality that set out data standards for the technical and privacy considerations of collating STBBI data at the local, state and national levels (19).…”
Section: Challenges and Enablersmentioning
confidence: 99%